IMPLEMENTASI METODE STAD DENGAN BANTUAN SEMPOA PADA MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN DUA ANGKA - Sarah Mutmainah; Wida Rachmiati; Juhji Juhji (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2019)
This research is motivated by the low student learning outcomes.student laziness can be caused by ineffective teaching and learning processes, the teacher is not right in determining the learning model and does not use teaching aids as a medium for learning mathematics, this results in the low student learning outcomes, the purpose of this research is to find out the activities of student and teachers in mathematics learning the addition and subtraction of two-digit numbers in improving student learning outcomes by using abacus media, the method used is classroom action research, research design using chemistry and mc. Design taggart which consists of four steps namely planning the implementation of observation and reflection which carried out two cycles, the subjects og this study were all students of class 1 MI AL-HUSNA Pasirnangka.the results of the study show that the use of abacus media can improve student learning outcomes MI Al-Husna Pasirnangka in terms of student activities in the learning process and learning outcomes this can be seen from the percentage of learning process activities and learning outcomes in cycle 1 that is 50%, then an increase in cycle II the percentage of learning process activities and learning outcomes in cycles II is 90%.